A critical view on the mobility need in high-competence organisations - Laugen, Bjørge Timenes; Lassen, Claus (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
Our objective in this paper is to investigate the relationship between mobility need in Danish high competence organisations and ICT. In section 1 we begin by introducing different theoretical perspectives on mobility and ICT. In section 2 we will explore the amount and characteristics of long-distance work-related mobility among the employees in two Danish high competence organisations. This section will methodologically be based on a multiple-case study design, which involves a survey and in-depth interviews considering transport work for the employees in the two selected cases. Finally, in section 3 we will analyse the potential for reduction of mobility needs in companies through increased use of ICT. This section will partly be based on the results from the multiple-case study and partly on the experiences from the research project Nettlaer, which focuses on how effective training and learning can be carried out supported by ICT tools. We end the paper by reflecting on the limitations and possibilities of using ICT as a tool for transport reductions in Danish high competence organisations.